The Effects of Colleges and Universities on Local Labor Markets - Beeson, Patricia; Montgomery, Edward (The Review of Economics and Statistics, 1993)
Despite the presence of anecdotal evidence linking regional economic growth and the presence of quality universities in such areas as the Silicon Valley in California and Route 128 in Boston, there have been few systematic studies of the relationship between universities and local economies. In this paper we examined the relationship between four measures of the quality or extent of activities of colleges and universities in an area and various measures of the local labor market activity, including employment, income and migration.